Pedagogical support in training physics teachers for the development and organization of extracurricular activities of schoolchildren - Antonova, N. A.; Kislitsyna, A. A. (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. The article studies the urgent problem of training physics teachers for the development and organization of extracurricular activities of schoolchildren. Extracurricular activities play an important role in the formation of students’ interest in science, the development of their creative potential and practical skills. However, the effectiveness of this work largely depends on the level of teachers’ willingness to implement it. The article reveals the main tasks of extracurricular activities and suggests ways to implement them in the framework of designing extracurricular activities. Goal. The tasks that must be solved in the process of designing extracurricular activities are defined, as well as the conditions that the extracurricular activity program must meet. Materials and methods. The article presents a developed program for training physics teachers to design extracurricular activities. The program includes theoretical and practical modules aimed at mastering modern pedagogical technologies, methods of organizing research and project work, as well as principles of interaction with students. The program includes assignments that allow teachers to practice the skills of developing extracurricular activities, conducting experiments, organizing scientific quests, and other forms of work. Results and discussion. The methodological possibilities of preparing a physics teacher for graduate studies at SUSGPU within the framework of the course Designing Extracurricular Activities of Students (in physics-mathematical set) are considered. The tasks are aimed at developing the ability to develop scenarios for classes, select educational materials and organize interaction with students. A special assignment is a test assignment: it is accompanied by assessment criteria that correspond to all the necessary aspects that must be implemented during the training. A fragment of the program was implemented in classes with undergraduates of physics and mathematics education. The proposed assignments include theoretical and practical aspects. The main problems that arise in the process of solving problems in the design of extracurricular activities are identified. Conclusion. The conducted research will be useful for university teachers, methodologists and physics teachers interested in improving the quality of extracurricular activities with schoolchildren. The proposed program and tasks can be used in the teacher training system, as well as in the training of students of pedagogical specialties